Study on Hydrodynamic Characteristics of the Raft-type Wave-Powered Desalination Device - Zheng, Siming (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis proposes a new raft-type wave-powered desalination device that can convert wave power into hydraulic energy and use reverse osmosis (RO) to directly desalinate seawater. Both analytical and numerical methods are used to study the hydrodynamic characteristics of the device. Further, the thesis investigates the maximum power extraction and multiple parameter effects on power absorption and averaged permeate water flux. Lastly, it proposes and assesses two power extraction enhancing strategies. The thesis offers a valuable and important reference guide to ocean-wave-and-structure interaction and wave-powered seawater desalination for scientists and engineers alike.